Geospatial Analysis for Assessing the Socioeconomic Conditions in Resettlement Housing Schemes in Siribopura, Hambantota - Hemakumara, G.P.T.S.; Subhashini, W.A.S. (Department of Estate Management and Valuation, Faculty of Management Studies and Commerce, 2018)
This study based on GIS analysis is intended to provide an overview of socioeconomic conditions in the resettlement housing scheme established in Siribopura, Hambantota to rehabilitate displaced persons. Several variables such as monthly income, and house and land values were checked for this purpose. Data were gathered from primary and secondary sources. The primary methods were open discussion and questionnaire survey while secondary methods were relevant documentation and websites. Siribopura, which is located in the Hambantota District was the main resettlement area. Majority of people resettled here are those displaced by the tsunami and certain development projects. The variables were checked using discriminate analysis. As per the results, 62.5% or majority of people in the tsunami resettlement area experience a poor quality of life. In the resettlement area set aside for those displaced by the development projects, the majority (90.6%) lead a quality life. Good income generation is the main reason for that. This study makes an important contribution by comparing the socioeconomic lives of the different groups of people and making an assessment about the resettlement project for the benefit of policy makers.
Keywords: Discriminate, Development, Rehabilitation, Resettlement, Housing